A Comparison of Immobilised Triphenylphosphine and 1‐Hydroxybenzotriazole as Mediators of Catch‐and‐Release Acylation Under Flow Conditions. Issue 5 (1st February 2022) - Tadros, Joseph; Dankers, Christian; Jurisinec, Ashley; Menti‐Platten, Maria; Aldrich‐Wright, Janice R.; Gordon, Christopher P.
Abstract: Described herein is a comparative study of immobilised triphenylphosphine (PS‐PPh3 ) and 1‐hydroxybenzotriazole (PS‐HOBt) to mediate amide couplings under continuous flow. Compared to Appel‐type amidations (PS‐PPh3 ), the developed 'catch‐and‐release' approach (PS‐HOBt) afforded near‐quantitative amide conversions. Utilising this strategy, sulfonyl chloride amenability enabled facile access to an expanded library of sulfonate and sulfonamides. Post‐constructional peptide modification was also demonstrated, affording two N β ‐functionalised pentapeptides in high yields and purities. In contrast to frequently utilised coupling agents, the PS‐HOBt resin could be recycled six times without a reduction in efficacy or regeneration requirements. Abstract : A 'catch‐and‐release' assessment of immobilised triphenylphosphine (PS‐PPh3 ) and 1‐hydroxybenzotriazole (PS‐HOBt) as facilitators of acylation‐mediated amide couplings is described. Through evaluations of reaction temperatures, substrate stoichiometries, solvents, and flow rates, we report findings in favour of PS‐HOBt over PS‐PPh3 .